Infant with SVT: Case Report - Bhattacharjee, Biplob; Biswas, Rajat Sanker Roy; Uddin, Md Salah; Rahman, Md Mukhlesur; Ahmed, Md Khurshed; Sultan, Md Ashraf Uddin (University Heart Journal, 2012)
A one and half year old child presented with lethargy and unwilling to take food for 2 days. He had history of unusual cry with a history of pneumonia 2 month back. After getting high heart rate on auscultation, a 12 lead ECG was done and diagnosed as a case of supra ventricular tachycardia (SVT). He was managed by using injection adenosine intravenously by which he was reverted to sinus rhythm. In this case, the treatment strategies of SVT in children will be discussed with other option also. DOI: http://dx.doi.org/10.3329/uhj.v7i2.10851 University Heart. Journal Vol. 7, No. 2, July 2011